Characterization of in vitro antioxidant, antitumor and anti-inflammatory properties of plant species from Rosaceae family - Garcia-Oliveira, Paula (2022)
Since ancient times, humans have employed different plant species to prepare traditional remedies and treat diseases, due to the health-promoting effects associated with these plants. Among them, several species belonging to the Rosaceae family, namely Agrimonia eupatoria L., Filipendula ulmaria (L.) Maxim. and Rosa canina L., which have been used in different preparations, like infusions, decoctions or tinctures, to treat diverse illnesses and diseases [1]. Nowadays, the search for natural derived ingredients has prompted the study of these traditional plants. The present work aimed to evaluate the biological properties of the above-mentioned Rosaceae species, in order to promote their applications in different sectors. Antioxidant activity was evaluated by different in vitro assays: 2,2-diphenylpycrilhydrazyl (DPPH) radical scavenging assay, thiobarbituric acid reactive substances (TBARS) assay for inhibition of lipid peroxidation, OxHLIA assay for inhibition of oxidative hemolysis, and reducing power determination. Antitumor activity was tested against four tumor cell lines: MCF-7, CaCo, AGS and NCI-H460. Finally, anti-inflammatory activity was assessed by the inhibition of inflammation on lipopolysaccharide-induced RAW264.7 murine macrophages. Considering the results, all plant extracts showed antioxidant effects in the tested assays, especially F. ulmaria. All tested extracts also displayed relevant antitumor effects against the four tested tumor cell lines, mostly F. ulmaria, which exhibited the lowest growth inhibition 50 values (GI50) ranging from 34 to 86 μg/mL of extract, presenting a noteworthy cytotoxic effect. Finally, R. canina showed significant anti-inflammatory effects, with effective concentration 50 values (EC50) of 20 μg/mL of extract. Therefore, the studied plants may be considered as promising natural sources of bioactive compounds with multifunctional biological properties for the development of several biobased applications.